Definitions, adjudication, and reporting of pulmonary embolism–related death in clinical studies: A systematic review. (31st July 2019) - Kraaijpoel, Noémie; Tritschler, Tobias; Guillo, Enora; Girard, Philippe; Le Gal, Grégoire
Abstract: Background: Pulmonary embolism (PE)–related death is a component of the primary outcome in many venous thromboembolism (VTE) studies. The absence of a standardized definition for PE‐related death hampers study outcome evaluation and between‐study comparisons. Objectives: To summarize definitions for PE‐related death used in recent VTE studies and to assess the PE‐related death rate. Patients/Methods: A systematic literature search was conducted on 26 April 2018 from 1 January 2014 up to the search date in MEDLINE, Embase, and CENTRAL. Cohort studies and randomized trials in which PE‐related death was included in the primary outcome were eligible. Screening of titles, abstracts, and full‐text articles, and data extraction were independently performed in duplicate by two authors. Study outcomes included the definition for PE‐related death, VTE case‐fatality rate, and death due to PE rate. Descriptive statistics were used to analyze the data. Results: Of the 6807 identified citations, 83 studies were included of which 27% were randomized trials, 31% were prospective, and 42% retrospective cohort studies. Thirty‐five studies (42%) had a central adjudication committee. Thirty‐eight (46%) reported a definition for PE‐related death of which the most frequently used components were "autopsy‐confirmed PE" (50%), "objectively confirmed PE before death" (55%), and "unexplained death" (58%). Median VTE case‐fatality rate was 1.8% (interquartile range, 0.0‐13). Conclusions: Only half of the included studies reported definitions for PE‐related death, which were very heterogeneous. Case‐fatality rate of VTE events varied widely across studies. Standardization of the definition and guidance on adjudication and reporting of PE‐related death is needed.